A tailored educational intervention improves doctor's performance in managing depression: a randomized controlled trial. Issue 1 (30th August 2011) - Shirazi, Mandana; Lonka, Kirsti; Parikh, Sagar V.; Ristner, Gunilla; Alaeddini, Farshid; Sadeghi, Majid; Wahlstrom, Rolf
Abstract Rational and objectives To assess the effects of a tailored and activating educational intervention, based on a three‐stage modified Prochaska model of readiness‐to‐change, on the performance of general physicians in primary care (GPs) regarding management of depressive disorders. Methods Parallel group, randomized control trial. Primary hypothesis was that performance would improve by 20 percentage units in the intervention arm. The setting was primary care in southern Tehran. The participants were 192 GPs stratified on stage of readiness‐to‐change, sex, age and work experience. The intervention was a 2‐day interactive workshop for a small group of GPs' at a higher stage of readiness‐to‐change ('intention') and a 2‐day interactive large group meeting for those with lower propensity to change ('attitude') at the pre‐assessment. GPs in the control arm participated in a standard educational programme on the same topic. The main outcome measures were validated tools to assess GPs' performance by unannounced standardized patients, regarding diagnosis and treatment of depressive disorders. The assessments were made 2 months before and 2 months after the intervention. Results GPs in the intervention arm significantly improved their overall mean scores for performance regarding both diagnosis, with an intervention effect of 14 percentage units (P = 0.007), and treatment and referral, with an intervention effect of 20 percentage units (P < 0.0001). The largest improvement after the intervention appeared in the small group: 30 percentage units for diagnosis (P = 0.027) and 29 percentage units for treatment and referral (P < 0.0001). Conclusions Activating learning methods, tailored according to the participants' readiness to change, improved clinical performance of GPs in continuing medical education and can be recommended for continuing professional development.